Pyrimethamine significantly lowers cerebrospinal fluid Cu/Zn superoxide dismutase in amyotrophic lateral sclerosis patients with SOD1 mutations. Issue 6 (9th June 2017) - Lange, Dale J.; Shahbazi, Mona; Silani, Vincenzo; Ludolph, Albert C.; Weishaupt, Jochen H.; Ajroud‐Driss, Senda; Fields, Kara G.; Remanan, Rahul; Appel, Stanley H.; Morelli, Claudia; Doretti, Alberto; Maderna, Luca; et al.
Abstract : Objective: Cu/Zn superoxide dismutase (SOD1) reduction prolongs survival in SOD1‐transgenic animal models. Pyrimethamine produces dose‐dependent SOD1 reduction in cell culture systems. A previous phase 1 trial showed pyrimethamine lowers SOD1 levels in leukocytes in patients with SOD1 mutations. This study investigated whether pyrimethamine lowered SOD1 levels in the cerebrospinal fluid (CSF) in patients carrying SOD1 mutations linked to familial amyotrophic lateral sclerosis (fALS/SOD1). Methods: A multicenter (5 sites), open‐label, 9‐month‐duration, dose‐ranging study was undertaken to determine the safety and efficacy of pyrimethamine to lower SOD1 levels in the CSF in fALS/SOD1. All participants underwent 3 lumbar punctures, blood draw, clinical assessment of strength, motor function, quality of life, and adverse effect assessments. SOD1 levels were measured in erythrocytes and CSF. Pyrimethamine was measured in plasma and CSF. Appel ALS score, ALS Functional Rating Scale–Revised, and McGill Quality of Life Single‐Item Scale were measured at screening, visit 6, and visit 9. Results: We enrolled 32 patients; 24 completed 6 visits (18 weeks), and 21 completed all study visits. A linear mixed effects model showed a significant reduction in CSF SOD1 at visit 6 ( p  < 0.001) with a mean reduction of 13.5% (95% confidence interval [CI] = 8.4–18.5) and at visit 9 ( p  < 0.001) with a mean reduction of 10.5% (95% CI = 5.2–15.8). Interpretation: Pyrimethamine is safe and well tolerated in ALS. Pyrimethamine is capable of producing a significant reduction in total CSF SOD1 protein content in patients with ALS caused by different SOD1 mutations. Further long‐term studies are warranted to assess clinical efficacy. Ann Neurol 2017;81:837–848